2011
DOI: 10.2459/jcm.0b013e3283439746
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cilostazol in the heart

Abstract: Cilostazol is a selective phosphodiesterase 3 (PDE3) inhibitor approved by the Food and Drug Administration for treatment of intermittent claudication. It has also been used in bradyarrhythmic patients to increase heart rates. Recently, cilostazol has been shown to prevent ventricular fibrillation in patients with Brugada syndrome. Cilostazol is hypothesized to suppress transient outward potassium (Ito) current and increase inward calcium current, thus, maintaining the dome (phase 2) of action potential, decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 74 publications
0
48
0
Order By: Relevance
“…Moreover, cAMP-dependent signaling is expected from animal studies to have neuroprotective effects in the cochlea [23,24] . PDE, the enzyme that hydrolyzes cGMP and cAMP to their inactive forms, has been classified into 11 isoenzymes [25] . PDE3 has high affinity for both cGMP and cAMP, and cAMP hydrolysis by PDE3 is 10 times greater than cGMP hydrolysis in terms of amount [25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cAMP-dependent signaling is expected from animal studies to have neuroprotective effects in the cochlea [23,24] . PDE, the enzyme that hydrolyzes cGMP and cAMP to their inactive forms, has been classified into 11 isoenzymes [25] . PDE3 has high affinity for both cGMP and cAMP, and cAMP hydrolysis by PDE3 is 10 times greater than cGMP hydrolysis in terms of amount [25] .…”
Section: Discussionmentioning
confidence: 99%
“…PDE, the enzyme that hydrolyzes cGMP and cAMP to their inactive forms, has been classified into 11 isoenzymes [25] . PDE3 has high affinity for both cGMP and cAMP, and cAMP hydrolysis by PDE3 is 10 times greater than cGMP hydrolysis in terms of amount [25] . Cilostazol is a selective PDE3 inhibitor and mainly increases the amount of cAMP by inhibiting cAMP degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This unique feature may contribute to the observed safety profile of cilostazol, and several studies have suggested a beneficial effect of cilostazol in arrhythmia prevention. 6 In this issue of the Journal, Lee et al provide more evidence regarding the benefit of adding cilostazol to DAPT ["triple antiplatelet therapy" (TAPT)] in reducing post-PCI clinical events. 7 In the primary analysis of the CILON-T (influence of CILostazol-based triple antiplatelet therapy ON ischemic complication after drug-eluting stent implantation) trial, 8 TAPT did not show superiority in reducing the composite of adverse cardiovascular outcomes after drug-eluting stent implantation despite greater reduction in platelet reactivity assessed by the VerifyNow P2Y12 assay [~45 P2Y12 reaction units (PRU)] compared with DAPT.…”
Section: Article P 2581mentioning
confidence: 99%
“…Third, cilostazol causes systemic vasodilation, thus producing reflex adrenergic stimulation 14) . Finally, cilostazol may cause a positive chronotropic effect due to its inhibitory effects on adenosine uptake 21) or its antagonizing adenosine tri- Data are given as medians (interquartile range), n (%) or mean differences (95% CI). Log-transformed data HR heart rate p 0.05 (compared with dual antiplatelet therapy), p 0.05 (compared with the baseline within-group).…”
Section: Efficacy and Safety Assessments For Treatment With Tat Versumentioning
confidence: 99%